Prevalence of depression and anxiety among university matriculation students in Malaysia: a case study - Mohamed, Luqman Hafidz; Jaafar Sidek, Mohd Farid; Zulkifli, Muhammad Firdaus; Abd. Rahman, Mohamed (Springer Nature Singapore, 2026)
Abstract The world is experiencing a rise in mental health issues among students of institutions of higher learning due to academic pressures, financial burdens, and adaptation challenges. It is essential to understand the mental health status of stu dents at the tertiary education level. Therefore, this paper aims to examine the prev alence of depression and anxiety among the tertiary education students and the relationship between individual characteristics, behaviours, and mental states of the students using the PHQ-9 and GAD-7 screening assessment tools to screen for depression and anxiety respectively. A sample of student respondents from the local university matriculation centre in Malaysia was taken for this study. Students volun tarily completed a survey form comprising three main constructs: demographic characteristics, behavioural patterns, and anxiety and depression. The data were analysed using descriptive statistics and Pearson correlation coefficients to identify potential relationships between variables. Subsequently, multiple linear regression analysis was conducted. Of 41 respondents, a high response rate was obtained from female students, those enrolled in science programs, individuals without physical disabilities, students who consumed two meals per day, those who engaged in less than 10 h of self-study per week, and those experiencing moderate levels of stress. Psychological measures include anxiety severity scores (GAD-7) with an average score of 6.8 (SD = 4.875). Meanwhile, depression severity score (PHQ-9) has a mean of 9.07 (SD = 6.747). Results showed a statistically significant association between BMI and anxiety severity; t = 2.68 (p = 0.011). Whereas the data shows strong association between meals taken per day and anxiety severity with the depression severity; t = −3.462 (p = 0.001) and t = 4.377 (p = 0.000) respectively. In conclusion, the respondents exhibited varying levels of depression and anxiety, which were significantly influenced by certain risk factors. The results indicate the need for further evaluation and improvement, as well as the potential to identify new key measures and risk factors.